Cardiovascular complications of anorexia nervosa: A systematic review. Issue 3 (29th December 2015) - Sachs, Katherine V.; Harnke, Ben; Mehler, Philip S.; Krantz, Mori J.
ABSTRACT: Objective: Anorexia nervosa portends the highest mortality among psychiatric diseases, despite primarily being a disease of adolescents and younger adults. Although some of this mortality risk is attributable to suicide, many deaths are likely cardiovascular in etiology. Recent studies suggest that adverse myocardial structural changes occur in this condition, which could underlie the increased mortality. Given limited prevalence of severe anorexia there is a paucity of clinical and autopsy data to discern an exact cause of death. Methods: Given this background we conducted a systematic review of the medical literature to provide a contemporary summary of the pathobiologic sequelae of severe anorexia nervosa on the cardiovascular system. We sought to elucidate the impact of anorexia nervosa in four cardiovascular domains: structural, repolarization/conduction, hemodynamic, and peripheral vascular. Results: A number of cardiac abnormalities associated with anorexia nervosa have been described in the literature, including pericardial and valvular pathology, changes in left ventricular mass and function, conduction abnormalities, bradycardia, hypotension, and dysregulation in peripheral vascular contractility. Despite the prevalent theory that malignant arrhythmias are implicated as a cause of sudden death in this disorder, data to support this causal relationship are lacking. Discussion: It is reasonable to obtain routine electrocardiography and measurements of orthostatic vital signs in patients presenting with anorexia nervosa. Echocardiography is generally not indicated unless prompted by clinical signs of disease. Admission to an inpatient unit with telemetry monitoring is recommended for patients with severe sinus bradycardia or junction rhythm, marked prolongation of the corrected QT interval, or syncope.